Lietuviškų knygų leidyklos Vakarų Europoje 1945-1952 m. - Misiūnas, Remigijus (Knygotyra, 2024)
There were 38 Lithuanian emigrant publishing houses in Western Europe between 1945 and 1952. Lithuanian books were also published in some Western European countries, including West Germany, Austria, and Sweden. Private publishing houses constituted the largest group among Lithuanian publishing houses. The most famous was J. Lenklaitis’s "Pajūris," followed by the publishing houses of brothers A., P., Vl. Šulčas’s "Sudavija," and L. Vismantas (later J. Remeikis) "Venta." Other private publishing houses in Western Europe included A. Giedrailis’s "Giedra," T. Vizgirda’s "Aufbau," J. Akšys’s "Žalgiris," B. Jacikevičius’s "Pašvaistė," S. Miglinas’s "Elementis," J. Narbutas and P. Indreika’s "P. Abelkis," A. Ružancovas’s "Kaimynai," J. Šlajus’s "Tėviškė," K. Jūra’s "Lithuania," and P. Leonas’s "Mundus." There were also two cooperative and four stock company publishing houses. Additionally, there were some Lithuanian publishing houses that did not fit into any specific group, as they had sporadic publications, such as "Aitvaras," "Lux," "Nauja mintis," "Almus," "Lituanican," "Perkūnas," "Ramybė," "Romuva," "Sodyba," "Talalgis," "Vaidilė," "Viltis," and "Akiratis." Most Lithuanian publishing houses in Western Europe were founded in the early years after the war (1945-11, 1946-13). Twelve of them operated for one year, nine for two years, three for three years, six for four years, two for five years, and only one for six years. There was competition among publishing houses for the small Lithuanian emigrant book market. Only a few publishing houses remained and operated. Many of the owners and managers of Lithuanian publishing houses began this work only in emigration, but the book publishing traditions that had been established in Lithuania were carried over to Western Europe. Publishing in the early years of the war had a commercial basis, with almost every book generating profit. Another commercial indicator was the dominance of private publishing houses. The experience of Lithuanian emigrant book publishing from 1945 to 1952 influenced the later work of Lithuanian publishing houses in Western Europe, North and South America, and Australia.